Internet governance, multi-stakeholder models, and the IANA transition: shining example or dark side?. Issue 2 (2nd July 2016) - Hill, Richard
ABSTRACT: Multi-stakeholder models refer to decision-making processes that involve a wide consultation of all interested parties. It has been stated that one particular version of such models is widely used in internet governance and has been very successful in achieving desirable outcomes. This paper shows that in fact no single multi-stakeholder model is used for internet governance. It then examines the IANA function, which is governed by a particular version of the multi-stakeholder model, and the current discussions regarding the reduction of the role of the US government in that governance (the so-called 'IANA transition'). The paper argues that the IANA transition is not a good example of best practices for multi-stakeholder models in internet governance.